LEARNING STRATEGY EMPLOYED BY EFL STUDENTS IN A LISTENING COMPREHENSION CLASS - Lilik Handayani (Educate, 2014)
Lilik Handayani Politeknik Perkapalan Negeri Surabaya (lily9.handayani@gmail.com) Abstract The present study was a case study undertaken to investigate the learning strategy employed by an EFL student and improvement of his listening comprehension. Participant‟s learning strategy was measured by Strategy Inventory for Language Learning (SILL) questionnaire and Strategic Listening Interview (SLI). The participant‟s listening comprehension skill was measured by an EFL listening comprehension test. The result of SILL questionnaire was calculated and analyzed to determine the most dominantly applied learning strategy. It was triangulated to the result of SLI, whereas the result of listening comprehension test was linked to the learning strategy. The findings revealed that the higher the level of strategic listening score the student obtained, the higher the score he attained on the listening comprehension test and vice versa. Keywords: learning strategy, SLI, SILL